Synthesis and Characterization of Sugarcane Bagasse Based Activated Carbon: Effect of Impregnation Ratio of ZnCl2 - Joshi, Sahira; K.C., Bishnu (Journal of Nepal Chemical Society, 2020)
Series of activated carbons (ACs) have been prepared from Sugarcane bagasse powder by ZnCl2 activation at various impregnation ratios of ZnCl2 to Sugarcane bagasse powder of 0.25:1, 0.5:1, 1:1 and 2:1 by weight. Characteristics of the activated carbons (ACs) were determined by iodine number, methylene blue number, surface area, scanning electron microscopy (SEM) and x-ray diffraction. Iodine number (IN) indicated that, microporosity of the AC were increased with increasing impregnation ratio ZnCl2 to Sugarcane bagasse upto 1:1 then started to decrease. However, mesoporosity as well as surface area was increased progressively. The maximum value of iodine number (868 mg/g) was achieved in the AC prepared at impregnation ratio of ZnCl2 to sugarcane bagasse 1:1. SEM micrographs also show the presence of well developed pores on its surface of AC-1. The broad peaks in the XRD patterns indicated that, all the ACs is amorphous materials. From results, it is concluded that ZnCl2 concentration used in impregnation is effective for development of porosity and surface area of the AC prepared from Sugarcane bagasse.